Pengaruh Investasi, Tenaga Kerja, Inflasi, san Konsumsi terhadap Pendapatan Domestik Regional Bruto - Jessica Ng; Angelina Angelina; Ketherine Alvia (IPM2KPE, 2022)
This study aims to assess the Effect of Investment, Labor, Inflation, and Consumption on Gross Regional Domestic Income of North Sumatra for the 2017-2020 period. This research method is descriptive quantitative. The sample of this research is 120 data on the Gross Regional Domestic Income of North Sumatra for the 2017-2020 period. Method of data analysis using multiple linear regression test. The results showed, partially the results of the t test are as follows, a) the investment variable has a tcount value of -0.262, with a sig value of 0.794, and a -tcount > -ttable value, namely -0.262 > -1.980; b) the labor variable has a tcount value of 23.450, with a sig value of 0.000, and a tcount > ttable that is 23.450>1.980; c) the inflation variable has a tcount value of -0.092, with a sig value of 0.927, and a value of -tcount > -ttable that is -0.092>-1.980; d) the consumption variable has a tcount value of 5.122, with a sig value of 0.000, and a tcount > ttable that is 5.122>1.980. The results of the F test are the Fcount value of 230.202, with a sig value of 0.000, and Ftable (120-4-1=115) of 2.45. Partially, investment and inflation variables have no impact on GRDP in North Sumatra during the 2017-2020 period. Meanwhile, partially labor and consumption have an effect on GRDP in North Sumatra during the 2017-2020 period. Simultaneously, investment, labor, inflation, and consumption affect the GRDP in North Sumatra during the 2017-2020 period. Keywords: Inflation, Investment, Consumption, Gross Regional Domestic Product, Labor